2018
DOI: 10.3389/fonc.2018.00033
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Receptors as Biomarkers in Human Breast Carcinoma Tissues

Abstract: Olfactory receptors (ORs) are known to be expressed in a variety of human tissues and act on different physiological processes, such as cell migration, proliferation, or secretion and have been found to function as biomarkers for carcinoma tissues of prostate, lung, and small intestine. In this study, we analyzed the OR expression profiles of several different carcinoma tissues, with a focus on breast cancer. The expression of OR2B6 was detectable in breast carcinoma tissues; here, transcripts of OR2B6 were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 56 publications
(69 reference statements)
3
52
0
Order By: Relevance
“…However, without the additional information provided by TIF-Seq2, those same RNA-seq datasets were not sufficient to confidently classify them as read-through transcripts. Interestingly, during the preparation of this work, a few cases have been investigated in detail and independently reported as fusion transcripts in agreement with our findings 26,27 .…”
Section: Identifying Read-through Transcriptssupporting
confidence: 90%
“…However, without the additional information provided by TIF-Seq2, those same RNA-seq datasets were not sufficient to confidently classify them as read-through transcripts. Interestingly, during the preparation of this work, a few cases have been investigated in detail and independently reported as fusion transcripts in agreement with our findings 26,27 .…”
Section: Identifying Read-through Transcriptssupporting
confidence: 90%
“…3g, h). Past reports evaluating the expression of chemosensory receptors in healthy tissues revealed the presence of multiple ORs 23,43 . We, therefore, examined the exclusivity of the ORs expressed in tumors.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the previously described compartments of Basal-like tumor, Classical tumor, Activated stroma, Normal stroma, immune, endocrine and exocrine, we also identified two new compartments, which we annotated as olfactory and histone. Interestingly, a study has associated the olfactory transduction pathway with pancreatic cancer risk 27 , and additional studies have shown the overexpression of olfactory receptors in multiple cancer types, including prostate 28,29 , bladder 30 and breast 31 cancers. In agreement with these studies, we found that our olfactory compartment was indeed present in prostate adenocarcinoma (PRAD), bladder urothelial carcinoma (BLCA), as well as several other cancer types (Supplementary Data 1).…”
Section: Discussionmentioning
confidence: 99%